State-of-the-Art Progress in Diverse Heterostructured Photocatalysts toward Promoting Photocatalytic Performance - Li, Haijin; Zhou, Yong; Tu, Wenguang; Ye, Jinhua; Zou, Zhigang (Advanced functional materials, 2015)
Semiconductor photocatalysts have received much attention in recent years due to their great potentials for the development of renewable energy technologies, as well as for environmental protection and remediation. The effective harvesting of solar energy and suppression of charge carrier recombination are two key aspects in photocatalysis. The formation of heterostructured photocatalysts is a promising strategy to improve photocatalytic activity, which is superior to that of their single component photocatalysts. This Feature Article concisely summarizes and highlights the state‐of‐the‐art progress of semiconductor/semiconductor heterostructured photocatalysts with diverse models, including type‐I and type‐II heterojunctions, Z‐scheme system, p–n heterojunctions, and homojunction band alignments, which were explored for effective improvement of photocatalytic activity through increase of the visible‐light absorption, promotion of separation, and transportation of the photoinduced charge carries, and enhancement of the photocatalytic stability. The state‐of‐the‐art progress of semiconductor/semiconductor heterostructured photocatalysts with diverse models is concisely summarized and highlighted, including type‐I and type‐II heterojunctions, Z‐scheme system, p–n heterojunctions, and homo junction band alignments, which are explored for effective improvement of photocatalytic activity through increase of the visible‐light absorption, promotion of separation and transportation of the photoinduced charge carries, and enhancement of the photocatalytic stability.